PENENTUAN CADANGAN PREMI DENGAN METODE NEW JERSEY PADA ASURANSI JOINT LIFE - TEWO, JENNE LALI; WIDANA, I NYOMAN; OKA, TJOKORDA BAGUS (E-Jurnal Matematika, 2018)
Joint Life insurance is an insurance that covered two individuals in one policy. The purpose of this research is to determine and to compare the reserve value of Joint Life insurance using New Jersey method and Prospective method with and without New Jersey method. The method that used in this research are New Jersey method, the participants of this assurance is a couple of husband and wife between 45 and 40 years old with 30 years period, interest levels at 6,5%. The results of this represent reserve value with New Jersey method always smaller, and the reserve value in the 30 years period have the same result using New Jersey method and Prospective method.